EDUCATIONAL TRANSFORMATION IN INDONESIA: REVIEWING THE POLICY LANDSCAPE AND LEARNING OUTCOMES - Aslan Aslan; Moch Isra Hajiri (Indonesian Journal of Education (INJOE), 2025)
Educational transformation in Indonesia is a response to global dynamics, technological developments, and the demands of 21st-century competencies. This study aims to comprehensively review the national education policy landscape and analyse learning outcomes as the impact of policy implementation, using a literature review method. Data sources include academic literature, official government reports, previous research findings, and national and international education statistics. The findings indicate that policies such as the Merdeka Curriculum, education digitalisation programmes, strengthening vocational education, and improving teacher capacity have contributed positively to improving literacy, numeracy, critical thinking skills, and digital competencies among students. However, challenges such as infrastructure gaps, regional disparities in quality, and uneven teacher quality still limit the optimisation of learning outcomes. These findings underscore the need for policy continuity and consistency, strengthening access equity, aligning the curriculum with the job market, and integrating character education to ensure that educational transformation produces globally competitive generations while contributing to sustainable national development.